Exploring preschool children's understanding of hospitals: Perceptions, experiences, and suggestions - Basaran, Mehmet; Karak, Merve (Elsevier Science Inc, 2026)
Purpose: This study aimed to examine preschool children's perceptions of hospitals through the draw-and-tell method. Methods: The research was conducted with 44 children aged 46 who had experienced at least one hospital visit. Data were collected through children's drawings and semi-structured interviews, and analyzed using reflexive thematic analysis. Results: Children described hospitals not only as medical spaces but also as environments interwoven with emotional, social, and developmental elements. Their conceptual associations predominantly focused on healthcare services and professionals, while their lived experiences ranged from fear and discomfort to playfulness and family support. The suggestions offered by children were largely shaped by their developmental needs, highlighting the importance of play, spatial comfort, and social support. Conclusion: The findings underscore the significance of child-centered approaches in healthcare and demonstrate that children are active agents in interpreting and improving their hospital experiences. Implications for practice: Hospital visits are not solely medical experiences for children; they also serve as emotional and social learning settings. Therefore, healthcare services should be redesigned to prioritize trust, meaningful interaction, and sensitivity to children's developmental and emotional needs. (c) 2025 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Preschool Children; Hospital Experience; Patient Participation; Child Perceptions